On the Issue of Retirement Age Increase in Russia - Olga Mihailovna Gvozdeva; Olga Mihailovna Krivtsova (Сибирское юридическое обозрение, 2012)
The article analyzes the trends in the Russian labor market which have developed due to demographic processes and social changes, and eventual problems in social welfare system. A possibility and an advisability of increase the Retirement age are estimated.